STUDY THE RELATIONSHIP BETWEEN BREMSSTRAHLUNG DOSE RATE AND THE ENERGY OF BETA RAY FOR DIFFERENT TYPES OF SHIELD: Nuclear Physics - Mkhaiber, Ahmed; Jarallah, Naz (Malaysian Journal of Science, 2022)
The dose rate for bremsstrahlung radiation from beta particles with energy (1.710) MeV and (2.28) MeV which comes from (32P and 90Y) beta source respectively have been calculated through six materials (polyethylene, wood, aluminum, iron, tungsten and lead) for first shielding material with thickness (x=1) mm which are putting between beta sources and second shield (polyethylene, aluminum and lead) with thickness (1, 2 &4) mm have been calculated. The distance between beta source and second shield is constant (D=1) cm. This dose rate was found by program called Rad Pro Calculator (version 3.26). The results of dose rate of beta particles were plotted as a function to the atomic number (Z) for first shield materials for each type and each thickness of second shield and each beta energy. The results of bremsstrahlung dose rate show clearly that this value increased with increased beta particle energy and the atomic number for second shield material. While bremsstrahlung dose rate reduced with rise of the width of second shield.